Revisiting legal protection of minors conscience against negative information influence (Journal of actual problems of jurisprudence, 2018)
The article analyses state measures on minors and children mind protection against negative information influence. The authors analyzed the legislation of the Republic of Kazakhstan and other countries on mass media and internet. Comparative analysis showed necessity of state regulation of children legal interests’ protection. Key words: information influence, children, children’s interests, media blackout, negative information.